M viral RNA segment of bunyaviruses codes for two glycoproteins, G1 and G2. - Gentsch, J R (1979)
Tryptic peptide digests of the two viral glycoproteins (G1 and G2) of snowshow hare (SSH) virus, La Crosse, La Crosse (LAC) virus, and an SSH/LAC recombinant virus which has a large (L)/medium (M)/small (S) RNA segment genome composition of SSH/LAC/SSH were analyzed by ion-exchange column chromatography. The analyses prove that the M RNA species of bunyaviruses codes for the two viral glycoproteins.